Evaluating Charpy Impact Signals Using Power Spectrum Densities: A Finite Element Method Approach - Ali, Mohd Basri Ali (Universiti Malaya, 2010)
Dynamic fracture properties of most engineering materials are generally assessed using the charpy test. The dynamic responses of the standard charpy impact machine are studied by running experiments using strain gauges and a specific data acquisition system in order to obtain the impact response and for this reason, the numerical analysis by means of the finite element method has been used to obtain the findings. In addition, the non-linear dynamic finite element is used for simulating the charpy impact test. The charpy test modelling was used in order to obtain the strain on the striker during the test. Two different velocities (5.18 m/s and 3.35 m/s) which are similar to the instrument charpy impact machine with the standard charpy modelling from the aluminium 6061 and low carbon steel 1050 as the rim material were used. A power spectrum density (PSD) is used to convert a signal from the time domain to the frequency domain using the fast Fourier transform (FFT) method. Related parameters of different materials, different velocities, energy absorbed, strain signals, PSD and the relationship between all the parameters were finally correlated and discussed. It was found that the modulus elasticity of materials and velocities were proportional to the energy absorbed, strain signals and PSD during the impact simulation.